Transdermal photothermal-pharmacotherapy to remodel adipose tissue for obesity and metabolic disorders - Zan, Ping (2022)
Despite the increasing prevalence of obesity, the current medications, which act indirectly on the central nervous system to suppress appetite or on the gastrointestinal tract to inhibit fat absorption, suffer from poor effectiveness and side effects. Here, we developed a transdermal mild photothermal therapy directly acting on the root of evil (subcutaneous white adipose depot) to induce its ameliorating remodeling (browning, lipolysis, and apoptosis), based on the injectable thermoresponsive hydrogel encapsulated with copper sulfide nanodots. Further, combining pharmaceutical therapy with codelivery of mirabegron leads to a strong therapeutic synergy. This method not only ensures high effectiveness and low side effects due to localized and targeted application but also remotely creates significant improvements in systemic metabolism. Specifically, as compared to the untreated group, it totally inhibits obesity development in high-fat-diet fed mice (15% less in body weight) with decreased masses of both subcutaneous (40%) and visceral fats (54%), reduced serum levels of cholesterol (54%)/triglyceride (18%)/insulin (74%)/glucose (45%), and improved insulin sensitivity (65% less in insulin resistance index). This self-administrable method is amenable for long-term home-based treatment. Finally, multiple interconnected signaling pathways are revealed, providing mechanistic insights to develop effective strategies to combat obesity and associated metabolic disorders.